Decitabine induction with myeloablative conditioning and allogeneic hematopoietic stem cell transplantation in high-risk patients with myeloid malignancies is associated with a high rate of infectious complications. (September 2020) - D'Angelo, Christopher R.; Hall, Aric; Woo, Kaitlin M.; Kim, KyungMann; Longo, Walter; Hematti, Peiman; Callander, Natalie; Kenkre, Vaishalee P.; Mattison, Ryan; Juckett, Mark
Highlights: Decitabine plus myeloablative allogeneic transplant was studied in myeloid cancers. Phase II clinical trial did not meet hypothesized improvement in overall survival. Decitabine and myeloablative combo led to high rates of infection and mortality. High rates of neutropenia and immunosuppression was the likely cause of infections. Abstract: Patients with high-risk myelodysplastic syndrome or acute myeloid leukemia have an increased risk of death following allogeneic hematopoietic stem cell transplantation (allo-HSCT). Decitabine has minimal non-hematologic toxicity and proven efficacy in myeloid diseases, and post-transplant cyclophosphamide (PTCy) has reduced rates of graft-versus-host-disease (GVHD). We hypothesized that decitabine induction with allo-HSCT and PTCy would improve outcomes in a high-risk myeloid disease population. We performed a phase-II trial of decitabine at 20 mg/m 2 for 10 days followed by allo-HSCT using a myeloablative regimen of fludarabine, IV busulfan and 4 Gy total body irradiation with PTCy for GVHD prophylaxis. Twenty patients underwent decitabine induction and 17 patients proceeded to transplant per protocol. Median overall survival from decitabine induction was 210 days (95 % CI 122-not reached). All patients developed grade 4 neutropenia after decitabine, eleven patients (55 %) developed grade 3−4 infections, and 5 cases were fatal. There were 5/20 (25 %) long-term survivors with a median follow-up of 3.6 years. Decitabine induction followed by myeloablative allo-HSCT in a high-risk population was associated with a high risk of infection and mortality related to enhanced immunosuppression. Further exploration of decitabine conditioning on reduced intensity platforms and improved infectious prophylaxis and screening may better mitigate toxicity (ClinicalTrials.gov (NCT01707004)).